Improving Students’ Reading Comprehension by Using Reciprocal Teaching Strategy - Maspufah, Maspufah (J-SHMIC : Journal of English for Academic, 2019)
Reading occupies large portion in teaching-learning activities, especially for English department students. It is reasonable since all their learning materials are in English. However, their ability in reading comprehension is low. Therefore, it is necessary to conduct a research to solve this problem. The purpose of this research was to find out whether Reciprocal Teaching strategy can solve and improve the students’ reading comprehension. Moreover, this research was also to find out what factors influence the improvement of the students’ reading comprehension. This research is action research. The participants of the research were the third semester students of 2018-2019 academic year which consisted of 13 students. The instruments used to collect the data were from observation checklists, field notes, interviews, and reading tests. After analyzing the data, it was found that reciprocal teaching strategy was able to improve the students’ reading comprehension ability. It could be seen from the improvement of their mean score in reading comprehension at the end of the cycle 1. The factors that influenced the improvement of their reading ability involved materials, teacher’s knowledge, students’ interaction, and assessment activities. To sum up, the implementation of reciprocal teaching strategy was able to provide positive results on their reading comprehension.